2018
DOI: 10.1021/acs.jpca.8b00577
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of Hydroxyphenyl-Substituted “Click” Triazoles

Abstract: The structural and optical properties of hydroxyphenyl-substituted-1,2,3-triazole molecules ("click" triazoles) are described. "Click" triazoles are prepared from the copper(I)-catalyzed azide-alkyne cycloaddition reactions. The alkyne-derived C4 substituent of a "click" triazole engages in electronic conjugation more effectively with the triazolyl core than the azide-derived N1 substituent. Furthermore, triazolyl group exerts a stronger electron-withdrawing effect on the N1 than the C4 substituent. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 72 publications
0
45
0
Order By: Relevance
“…Furthermore, the hydrogen bond strengthening or weakening could also be revealed based on monitoring the spectral shifts of vibrational modes involved in the formation of hydrogen bonds . The vibrational spectra of bip chromophore in the conjunct vibrational regions of the O‐H stretching mode have been shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the hydrogen bond strengthening or weakening could also be revealed based on monitoring the spectral shifts of vibrational modes involved in the formation of hydrogen bonds . The vibrational spectra of bip chromophore in the conjunct vibrational regions of the O‐H stretching mode have been shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The geometric optimizations of bip , bip‐open and bip‐pt were performed using DFT in the S 0 state and using TDDFT in the S 1 state. Especially, the TDDFT method has become a very useful tool to theoretically investigate the hydrogen bonding interaction that occurs in the excited states . In addition, Becke's three‐parameter hybrid exchange functional with Lee–Yang–Parr gradient‐corrected correlation (B3LYP functional) was selected in both the DFT and TDDFT methods .…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that the alkyne-derived substituent moiety of a "click" triazole can engage in electronic conjugation with the triazolyl core that may have profound influences on the optical properties of these compounds. 50 Photon reabsorption behavior of such compounds can be vexing for the development of energy efficient lightemitting materials, however, this could be advantageous for producing a composite emission color that facilitates selective detection of differentially substitutes triazole products during SPAAC reactions. The influence of the triazole moiety substitution patterns on the electrochemical and photophysical properties of the donor-acceptor groups has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%